Contribution of Organizational Commitment through Discipline, Professionalism, and Work Culture of Public Service Sector Employees - Andari, Andari; Nafiudin Nafiudin; Fatya Nisyah; Niken Widillahi (International Journal of Economics, Commerce, and Management, 2026)
This study aims to analyze the influence of work discipline, professionalism, and organizational culture on organizational commitment among employees in the Public Service Sector. Organizational commitment is an important factor that reflects employee loyalty and attachment to the institution, while the three independent variables are considered as internal factors that can strengthen this commitment. The method used in this study is associative quantitative with a multiple linear regression approach. Data were collected through distributing questionnaires to 46 respondents based on probability sampling techniques. Data processing and analysis in this study used SPSS software version 27. Based on the results of the study, it was found that there is a significant influence of work discipline on organizational commitment. In addition, professionalism has a significant effect on organizational commitment, organizational culture has a significant effect on organizational commitment. Based on simultaneous hypothesis testing, it is proven that work discipline, organizational culture, and professionalism jointly influence organizational commitment. While the amount of contribution is 54% to organizational commitment, while the remaining 46% of organizational commitment is influenced by other factors such as leadership style, motivation, competence, rewards, job satisfaction, and employee performance. Thus, this study confirms that to increase organizational commitment, government agencies need to strengthen a healthy work culture, enforce discipline, and encourage a professional attitude in the work environment.